2005
DOI: 10.1366/0003702053641496
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Thermal Gelation of Cellulose Ethers in situ Using Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy

Abstract: In this work attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy was used to probe the thermal gelation behavior of aqueous solutions of hydroxypropyl methylcellulose (HPMC), specifically thermal gelation and accompanying precipitation. Cloud point measurements are usually evaluated through turbidity in dilute solutions but the method cannot readily be applied to more concentrated or highly viscous solutions. From the ATR-FTIR data, intensity changes of the nu(CO) band marked the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Although the gelation of MC has been extensively studied by various analytical techniques (NMR, differential scanning calorimetry, IR attenuated total reflectance spectroscopy, small-angle neutron scattering, static and dynamic light scattering, and rheology) and the researchers have proposed different gelation mechanisms, the specific molecular interactions that govern this process is still unclear. However, the results of various studies, which were in good agreement one with another, indicated several factors and/or phenomena which play an important role in the gelation of MC [24,[51][52][53][54][55][56][57][58][59][60][61][62][63][64]:…”
Section: Colloidal Dissolution and Gelation As Processes Involved In mentioning
confidence: 52%
See 2 more Smart Citations
“…Although the gelation of MC has been extensively studied by various analytical techniques (NMR, differential scanning calorimetry, IR attenuated total reflectance spectroscopy, small-angle neutron scattering, static and dynamic light scattering, and rheology) and the researchers have proposed different gelation mechanisms, the specific molecular interactions that govern this process is still unclear. However, the results of various studies, which were in good agreement one with another, indicated several factors and/or phenomena which play an important role in the gelation of MC [24,[51][52][53][54][55][56][57][58][59][60][61][62][63][64]:…”
Section: Colloidal Dissolution and Gelation As Processes Involved In mentioning
confidence: 52%
“…Thus, the additives that impart a solubilizing effect (i.e., ethanol, propyleneglycol, PEG 400) raise the gel point of HPMC, whereas the additives that exhibit a coagulant effect (i.e., glycerol, sorbitol, and most electrolytes) lower the gel temperature. In the past decade, numerous studies on thermoreversible gelation behavior of HPMC solutions have been carried out [22][23][24][25][26].…”
Section: Specific Property Hydroxyethylcellulosementioning
confidence: 99%
See 1 more Smart Citation
“…In [1,2], in an investigation Table 3. The lines join the frequencies of normal vibrations for different conformers with comparable modes of vibration.…”
Section: Regionmentioning
confidence: 99%
“…Most temperature-sensitive polymeric excipients have a LCST too high to be useful for this purpose (e.g., cellulose ethers above 418C). 7 By contrast, poly(Nisopropyl acrylamide), PNIPA, exhibits the LCST at around 338C, 8 which is not significantly altered by saliva components or gastrointestinal fluids. 9 Owing to its LCST, PNIPA cross-linked hydrogels undergo intense volume phase-transitions.…”
Section: Introductionmentioning
confidence: 99%